2003
DOI: 10.1074/jbc.m306619200
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of Capsaicin-activated Currents in the Vanilloid Receptor TRPV1 Is Decreased by the Cyclic AMP-dependent Protein Kinase Pathway

Abstract: Proinflammatory prostaglandin E2 is known to sensitize sensory neurons to noxious stimuli. This sensitization is mediated by the cAMP-dependent protein kinase (PKA) signal pathway. The capsaicin receptor TRPV1, a non-selective cation channel of sensory neurons involved in the sensation of inflammatory pain, is a target of PKA-mediated phosphorylation. Our goal was to investigate the influence of PKA on Ca 2؉ -dependent desensitization of capsaicin-activated currents. By using site-directed mutagenesis, we crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
216
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(230 citation statements)
references
References 24 publications
(23 reference statements)
9
216
1
Order By: Relevance
“…6C, when applying our prolonged agonist exposure protocol (1 M capsaicin for 20 min), TRPV1-S116D-expressing cells displayed ϳ60% desensitization (R pH2/pH1 ϭ 0.37 Ϯ 0.01, n ϭ 506, n ϭ 5) as compared with 90% observed with TRPV1-WT (R pH2/pH1 ϭ 0.10 Ϯ 0.01%, n ϭ 409, n ϭ 8). We then asked whether the observed decrease in desensitization, which agrees with results reported by others (8,9), is because of decreased internalization of the S116D mutant. Using surface biotinylation/avidin pulldown assays, we found that in contrast to wild type channels, surface levels of TRPV1-S116D were not affected by capsaicin incubation, as revealed by the levels of the mutant protein, which remained similar to those of cells exposed to vehicle (Fig.…”
Section: Capsaicin Induced Trpv1 Internalization In a Dose-andsupporting
confidence: 80%
See 1 more Smart Citation
“…6C, when applying our prolonged agonist exposure protocol (1 M capsaicin for 20 min), TRPV1-S116D-expressing cells displayed ϳ60% desensitization (R pH2/pH1 ϭ 0.37 Ϯ 0.01, n ϭ 506, n ϭ 5) as compared with 90% observed with TRPV1-WT (R pH2/pH1 ϭ 0.10 Ϯ 0.01%, n ϭ 409, n ϭ 8). We then asked whether the observed decrease in desensitization, which agrees with results reported by others (8,9), is because of decreased internalization of the S116D mutant. Using surface biotinylation/avidin pulldown assays, we found that in contrast to wild type channels, surface levels of TRPV1-S116D were not affected by capsaicin incubation, as revealed by the levels of the mutant protein, which remained similar to those of cells exposed to vehicle (Fig.…”
Section: Capsaicin Induced Trpv1 Internalization In a Dose-andsupporting
confidence: 80%
“…TRPV1 desensitization is a process markedly depending on Ca 2ϩ and involves various intracellular signaling pathways (6). Thus, dephosphorylation by the phosphatase calcineurin of TRPV1 previously phosphorylated by protein kinase A (PKA) or Ca 2ϩ -calmodulin-dependent kinase II leads to TRPV1 desensitization (7)(8)(9)(10). Several other mechanisms like binding of molecules such as calmodulin (11)(12)(13), ATP (13), or AKAP150 (14) or the depletion of phosphoinositol 4,5-diphosphate from the plasma membrane (15-18) also modulate receptor desensitization.…”
mentioning
confidence: 99%
“…38 In contrast, phosphorylation by protein kinase A and protein kinase C has been proposed to slow desensitization in TRPV1 channels, 39,40 and protein kinase C has also been implicated in reversing desensitization of TRPM4 channels. 41 Ca 2+ /CaM regulated phosphorylation/dephosphorylation has also been proposed: phosphorylation of TRPC5 by myosin light chain kinase is associated with slowing of desensitization 42 and dephosphorylation of TRPV1 by calcineurin is reported to promote desensitization.…”
Section: Mechanism-ca 2+ -Regulated Kinases and Phosphatasesmentioning
confidence: 99%
“…Besides direct activation mechanisms, several molecules are able to act on TRPV1 via first activating their specific receptors and then initiating downstream signaling pathways leading to the sensitization of TRPV1. Indeed, bradykinin [183,184], ATP [185], lipoxygenase products [182,183], prostaglandins [186,187], histamine [188], various neurotrophins (NGF, neurotrophin-3 and -4) [91,102,184], TNF- [189,190], pro-inflammatory chemokines [191], and PAR2 [192,193] were all reported to sensitize TRPV1 via various signal transduction pathways. TRPV1 was shown to be modulated by the protein kinase C (PKC) [183,[194][195][196], phospholipase C (PLC), and phosphatidylinositol 4,5-bisphosphate (PIP 2 ) [184,[197][198][199][200] systems as well as by intracellular ATP [201].…”
Section: Activation and Sensitization Of Trpv1mentioning
confidence: 99%